Effects of ferumoxytol on quantitative PET measurements in simultaneous PET/MR whole-body imaging: a pilot study in a baboon model. - Ronald JH Borra; Hoon-Sung Cho; Spencer L Bowen; Ulrike Attenberger; Grae Arabasz; Ciprian Catana; Lee Josephson; Bruce R Rosen; Alexander R Guimaraes; Jacob M Hooker (SpringerOpen, 2025)
BACKGROUND Simultaneous PET/MR imaging depends on MR-derived attenuation maps (mu-maps) for accurate attenuation correction of PET data. Currently, these maps are derived from gradient-echo-based MR sequences, which are sensitive to susceptibility changes. Iron oxide magnetic nanoparticles have been used in the measurement of blood volume, tumor microvasculature, tumor-associated macrophages, and characterizing lymph nodes. Our aim in this study was to assess whether the susceptibility effects associated with iron oxide nanoparticles can potentially affect measured (18)F-FDG PET standardized uptake values (SUV) through effects on MR-derived attenuation maps. METHODS The study protocol was approved by the Institutional Animal Care and Use Committee. Using a Siemens Biograph mMR PET/MR scanner, we evaluated the effects of increasing concentrations of ferumoxytol and ferumoxytol aggregates on MR-derived mu-maps using an agarose phantom. In addition, we performed a baboon experiment evaluating the effects of a single i.v. ferumoxytol dose (10 mg/kg) on the liver, spleen, and pancreas (18)F-FDG SUV at baseline (ferumoxytol-naïve), within the first hour and at 1, 3, 5, and 11 weeks. RESULTS Phantom experiments showed mu-map artifacts starting at ferumoxytol aggregate concentrations of 10 to 20 mg/kg. The in vivo baboon data demonstrated a 53% decrease of observed (18)F-FDG SUV compared to baseline within the first hour in the liver, persisting at least 11 weeks. CONCLUSIONS A single ferumoxytol dose can affect measured SUV for at least 3 months, which should be taken into account when administrating ferumoxytol in patients needing sequential PET/MR scans. Advances in knowledge 1. Ferumoxytol aggregates, but not ferumoxytol alone, produce significant artifacts in MR-derived attenuation correction maps at approximate clinical dose levels of 10 mg/kg. 2. When performing simultaneous whole-body (18)F-FDG PET/MR, a single dose of ferumoxytol can result in observed SUV decreases up to 53%, depending on the amount of ferumoxytol aggregates in the studied tissue. Implications for patient care Administration of a single, clinically relevant, dose of ferumoxytol can potentially result in changes in observed SUV for a prolonged period of time in the setting of simultaneous PET/MR. These potential changes should be considered in particular when administering ferumoxytol to patients with expected future PET/MR studies, as ferumoxytol-induced SUV changes might interfere with therapy assessment.